Progress of the National Bobwhite Conservation Initiative - Donald F. McKenzie; John J. Morgan; Thomas V. Dailey (National Quail Symposium Proceedings, 2017)
Northern bobwhites (Colinus virginianus) have declined precipitously over 5 decades because of a decline in habitat, largely a result of agricultural intensification and inadequate management of natural plant succession. In response, quail biologists developed strategic and operational plans, and formed a national partnership of state and federal agencies, bobwhite institutions, non-government organizations, universities and private citizens. The early history of these efforts was reviewed in 2006 at the Sixth National Quail Symposium. Over the past 10 years, exponential growth occurred, including establishment of a home for national bobwhite conservation at the University of Tennessee, and funding from the National Fish and Wildlife Foundation, the United States Fish Wildlife Service Pitmann-Robertson (Federal Aid in Wildlife Restoration Program), individual state agencies and citizens. The result in 2016 is the National Bobwhite Conservation Initiative (NBCI), a 25-state consortium of state wildlife agencies and partners, led by the National Bobwhite Technical Committee and NBCI Management Board. In 2011, NBCI published an updated strategic restoration plan, and spatially-explicit planning tool, NBCI 2.0, followed in 2014 by an implementation plan, the NBCI Coordinated Implementation Program (CIP). We update the history of the NBCI, including changes in funding mechanisms, leadership, administration, and technical programs, and we assess current opportunities and the future of bobwhite conservation.
Keywords: northern bobwhite; Colinus virginianus; Pitmann-Robertson; conservation; plan